2024
DOI: 10.1001/jamaophthalmol.2023.6316
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the Vision Screening Pathway for School-Aged US Children

Isdin Oke,
Natalie Slopen,
Alison A. Galbraith
et al.

Abstract: This cross-sectional study uses a nationally representative survey of the US pediatric population to identify gaps in the vision screening pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…To the Editor In their article titled “Gaps in the Vision Screening Pathway for School-Aged US Children,” Oke et al discuss the “evidence of inequitable opportunities for access to vision screening and subsequent care experienced most often by socioeconomically vulnerable groups.” I wholeheartedly endorse this statement, and for a very personal reason: I was from one of those vulnerable groups.…”
mentioning
confidence: 81%
“…To the Editor In their article titled “Gaps in the Vision Screening Pathway for School-Aged US Children,” Oke et al discuss the “evidence of inequitable opportunities for access to vision screening and subsequent care experienced most often by socioeconomically vulnerable groups.” I wholeheartedly endorse this statement, and for a very personal reason: I was from one of those vulnerable groups.…”
mentioning
confidence: 81%
“…Eye care is a leading specialty referral in pediatric primary care, and many children may be referred for reasons other than failed vision screening. It might be valuable to know the percentage of ophthalmology referrals after instrument-based screening and how many of the referred children had completed a visit with an ophthalmologist—an additional area where potential racial, ethnic, and socioeconomic disparities may exist …”
mentioning
confidence: 99%
“…To the Editor In their analysis of data from the 2021 National Survey of Children’s Health, Oke et al demonstrated that children aged 6 to 18 years from historically marginalized racial and ethnic groups, low-income households, and non–English language speakers were less likely to receive vision screening and less likely to establish care with an eye specialist if they were screened …”
mentioning
confidence: 99%